2006
DOI: 10.1289/ehp.8551
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic Exposure and Type 2 Diabetes: A Systematic Review of the Experimental and Epidemiologic Evidence

Abstract: Chronic arsenic exposure has been suggested to contribute to diabetes development. We performed a systematic review of the experimental and epidemiologic evidence on the association of arsenic and type 2 diabetes. We identified 19 in vitro studies of arsenic and glucose metabolism. Five studies reported that arsenic interfered with transcription factors involved in insulin-related gene expression: upstream factor 1 in pancreatic β-cells and peroxisome proliferative-activated receptor γ in preadipocytes. Other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
206
2
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 303 publications
(216 citation statements)
references
References 74 publications
7
206
2
1
Order By: Relevance
“…Studies in this area of research have examined insulin secretion and glucose metabolism in cultured cells or laboratory animals exposed to highly toxic concentrations of As, which are incompatible with chronic exposures in humans. Therefore, data from these studies cannot be evaluated with respect to possible mechanisms of diabetes induced by environmental or occupational exposures and attempts to do so would inevitably yield confusing results (Navas-Acien et al, 2006). The following is a brief contextual review of laboratory studies that have examined the effects of As on processes directly related to glucose homeostasis.…”
Section: Laboratory Studies Of the Effects Of As On Glucose Metabolismmentioning
confidence: 99%
“…Studies in this area of research have examined insulin secretion and glucose metabolism in cultured cells or laboratory animals exposed to highly toxic concentrations of As, which are incompatible with chronic exposures in humans. Therefore, data from these studies cannot be evaluated with respect to possible mechanisms of diabetes induced by environmental or occupational exposures and attempts to do so would inevitably yield confusing results (Navas-Acien et al, 2006). The following is a brief contextual review of laboratory studies that have examined the effects of As on processes directly related to glucose homeostasis.…”
Section: Laboratory Studies Of the Effects Of As On Glucose Metabolismmentioning
confidence: 99%
“…[4][5][6]17,18 Studies conducted in different countries and also in Bangladesh revealed an association with arsenic exposure and diabetes. [4][5][6][7][8][9] According to the recent profile of Bangladesh International Diabetes Federation (BIDF), the prevalence of diabetes in the age group 30 to34 years was 4.5% and in the age group 35 to 39 years was 5.0%, while in the age group 60 to 64 years the prevalence (10.2%) was more than double. 19 The current study revealed a similar prevalence of diabetes among the age group 30 to 34 years (4.4%) and 35 to 39 years (5.0%).…”
Section: Discussionmentioning
confidence: 99%
“…3 Several studies have reported an association with arsenic exposure and diabetes mellitus. [3][4][5][6][7][8] Association of arsenic exposure with non-communicable diseases including Worldwide prevalence of diabetes mellitus is increasing in alarming way and is becoming a top cause of death. Every six seconds a person dies due to diabetes and it is projected that by 2030 diabetes will be the 7th leading cause of death.…”
Section: Introductionmentioning
confidence: 99%
“…Also, pentavalent arsenate un-couples mitochondrial oxidative phosphorylation by a mechanism associated to competitive substitution of arsenate for inorganic phosphate in the formation of adenosine triphosphate (NRC, 2001). Some researchers also found out its increased risk of predisposing to diabetes mellitus, immunotoxicity and haematotoxicity respectively (ATSDR, 2005;Navas-Acien et al, 2006). In addition, it also causes genotoxicity with an unclear mechanism.…”
Section: Introductionmentioning
confidence: 99%